WOMEN’S LEADERSHIP IN ISLAM IN INDONESIA AFTER THE REFORM ERA - Abidin, Muhammad (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2023)
The objectives of this research are (1) to understand the position of women according to Islamic law, and (2) to know the law regarding a woman in leadership, particularly according to Islamic law in the post-reform era in Indonesia. This research uses a qualitative method, which explains in detail the position and law of women in terms of leadership, especially according to Islamic law in Indonesia during the post-reform period. The type of research is normative, a study that draws sources from books with subjects themed around women's leadership. The object is the law concerning women. In the data collection stage, the researcher uses the technique of reading information and then recording the results obtained. The analysis technique is descriptive, meaning it is illustrated. From these techniques, the results obtained are as follows: the role of women in their existential development as leaders in Indonesia, especially The post-reform period continues to evolve. Some scholars, whether classical or contemporary, have differing opinions on female leadership, particularly in the interpretation of related verses and hadiths. Classical scholars argue that women are prohibited from leading, especially for public matters, while contemporary scholars have recently reinterpreted that Islam does not forbid women from holding positions or public offices. In fact, contemporary scholars understand contextually that there is no specific prohibition against women leading, and even if they become heads of state, it is allowed as long as they meet the requirements, are capable, willing, and able to take full responsibility, both before society, themselves, and the Creator.